Emotion-focused therapy for generalized anxiety - Watson, Jeanne C.; Greenberg, Leslie S. (American Psychological Association, 2017)
"Generalized anxiety disorder (GAD)--characterized by near-constant worry that often coincides with intense feelings of shame and despair--is a highly treatment-resistant disorder, with clients often relapsing after making some progress. Master therapists Jeanne Watson and Leslie Greenberg argue, however, that emotion-focused therapy (EFT) is uniquely capable of targeting the maladaptive emotional schemes that underlie GAD and helping clients maintain lasting, positive change. In this practical guide, Watson and Greenberg teach mental health practitioners how to employ EFT methods in their work with GAD clients. The authors first review EFT's conceptualization of GAD, emphasizing the key role that emotion plays in pervasive anxiety. They then translate those foundational principles into detailed techniques and strategies as they walk readers through the EFT process, beginning with the establishment of a healing therapeutic relationship. Chapters review different stages of EFT, describing specific therapeutic exercises, such as empty-chair and two-chair tasks, that allow clients to vocalize and directly address their deep-rooted emotional pain, anxieties, and relational injuries with significant others. Through this work, clients eventually learn to self-soothe and transform their maladaptive coping mechanisms into healthier ones. Sample client-therapist dialogues demonstrate how these EFT techniques can be applied in actual practice"--Publicity materials. (PsycINFO Database Record (c) 2017 APA, all rights reserved).